The Potential of Ramie Fiber as Reinforcement in Calcium Carbonate-Filled Polyester Resin Matrix Composites for Roofing Applications - Reinaldo, Reinaldo; Setyanto, Djoko (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Polymer matrix composite roofing materials available in the Indonesian market typically consist of 30%wt chopped strand mat glass fiber embedded in unsaturated polyester resin, filled with 30 parts per hundred resin (PHR) calcium carbonate. The aim of this research is to evaluate whether natural ramie fibers can potentially replace glass fibers. In the first stage of the study, we compared three types of natural fibers abundant in Indonesia: banana stem fibers, sugarcane bagasse, and ramie. Showed that ramie fiber performed the best. Its flexural strength, flexural modulus, and impact toughness were the highest, measured at 191.57 MPa, 6691 MPa, and 0.056 J/mm², respectively. In the second stage, we produced composite material specimens with the same composition as commercial roofing materials but replaced the glass fibers with ramie fibers. Compared to the material without ramie fibers, the composite reinforced with ramie fibers shows an increase in tensile strength to 47.53 MPa from 34.62 MPa, an increase in maximum water absorption over 14 days to 3.746% from 1.145%, and an improvement in the sound transmission class to 26 dB from 23 dB. Additionally, the ramie fibers did not significantly affect the density of the composite material. However, the inclusion of ramie fibers resulted in a reduction of the elastic modulus to 1324 MPa from 1630 MPa, and a higher mass loss in the TGA examination, at 86.95% compared to 74.65%. Ramie fiber composites achieve the minimum roofing requirement of 40 MPa tensile strength, thus having the potential to replace glass fibers.